2015
DOI: 10.1016/j.jembe.2014.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Ocean acidification does not impact shell growth or repair of the Antarctic brachiopod Liothyrella uva (Broderip, 1833)

Abstract: Marine calcifiers are amongst the most vulnerable organisms to ocean acidification due to reduction in the availability of carbonate ions for skeletal/shell deposition. However, there are limited long-term studies on the possible impacts of increased pCO 2 on these taxa. A 7 month CO 2 perturbation experiment was performed on one of the most calcium carbonate dependent species, the Antarctic brachiopod Liothyrella uva, which inhabits the Southern Ocean where carbonate ion saturation levels are amongst the lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 70 publications
2
42
0
Order By: Relevance
“…Cross et al (2018) found that punctae became narrower over the past 120 years, which partially explained the increase in shell density over this period. Overall, there appears to be little to no apparent effect on brachiopod morphology or chemistry with lower seawater pH (Cross et al, 2015(Cross et al, , 2016(Cross et al, , 2018.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Cross et al (2018) found that punctae became narrower over the past 120 years, which partially explained the increase in shell density over this period. Overall, there appears to be little to no apparent effect on brachiopod morphology or chemistry with lower seawater pH (Cross et al, 2015(Cross et al, , 2016(Cross et al, , 2018.…”
Section: Introductionmentioning
confidence: 96%
“…This applies to calcium carbonate shell-forming species, such as brachiopods and mollusks, because they are considered excellent archives documenting F. Ye et al: Variation in brachiopod microstructure and isotope geochemistry changes in environmental conditions affecting marine organisms (e.g. Kurihara, 2008;Comeau et al, 2009;Hahn et al, 2012Hahn et al, , 2014Watson et al, 2012;Cross et al, 2015Cross et al, , 2016Cross et al, , 2018Crippa et al, 2016a;Milano et al, 2016;Garbelli et al, 2017;Jurikova et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological implications of these changes are less well described and have largely been identified from organism responses in laboratory experiments lasting a few days to a few months (Riebesell & Gattuso, ). In recognition of the fundamental role played by seasonal phenotypic plasticity and genetic change across generations, long‐term experiments which allow for acclimation (Cross, Peck, & Harper, ; Cross, Peck, Lamare, & Harper, ; Hazan, Wangensteen, & Fine, ; Suckling et al., ) and/or adaptation potential in organisms with short generation times (Andersson et al., ; Collins, Rost, & Rynearson, ) are now being made. Although information from long‐term laboratory experiments is vital to reveal sensitivities of marine organisms, even they can still only predict responses from exposures of relatively short durations, of months or even a few years, to environmentally unrealistic conditions (Andersson et al., ; Riebesell & Gattuso, ).…”
Section: Introductionmentioning
confidence: 99%
“…Biological implications of these changes are less well described and have largely been identified from organism responses in laboratory experiments lasting a few days to a few months (Riebesell & Gattuso, 2015). In recognition of the fundamental role played by seasonal phenotypic plasticity and genetic change across generations, long-term experiments which allow for acclimation (Cross, Peck, & Harper, 2015;Cross, Peck, Lamare, & Harper, 2016;Hazan, Wangensteen, & Fine, 2014;Suckling et al, 2014) and/or adaptation potential in organisms with short generation times (Andersson et al, 2015;Collins, Rost, & Rynearson, 2014) are now being made. Although information from long-term laboratory experiments is vital to reveal sensitivities of marine organisms, even they can still only predict responses from exposures of relatively short durations, of months or even a few years, to environmentally unrealistic conditions experiments, including in situ mesocosms (Nagelkerken & Munday, 2015) and CO 2 vent sites (Fabricius et al, 2011;Hall-Spencer et al, 2008;Uthicke et al, 2016), are another common approach which allows for the investigation of impacts on more long-term scales and also often include responses at the community level and the physical, chemical and biological variability in their natural environments that cannot be recreated in laboratory experiments.…”
Section: Introductionmentioning
confidence: 99%